Miłość w włosko-polskiej konfrontacji językowej na podstawie ekwiwalencji przysłów - Wismont, Magdalena (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
The article takes on the subject of linguistic picture of the world concerning the love and equivalent proverbs in Italian and Polish languages. The analysis of lexicographical materials demonstrates identical perception of this feeling, confluences within syntax of equivalents (despite the affiliation to different groups of languages) and, several times, common origin of proverbs in either language. This provenance oscillates around Latin. All of this tangential points undoubtedly are result of common, European cultural heritage.